A Mass Balance Study of 14C‐Labeled JTZ‐951 (Enarodustat), a Novel Orally Available Erythropoiesis‐Stimulating Agent, in Patients With End‐Stage Renal Disease on Hemodialysis. Issue 6 (25th December 2019) - Pai, Sudhakar M.; Connaire, Jeffrey; Yamada, Hiroyuki; Enya, Seiji; Gerhardt, Barbara; Maekawa, Michihide; Tanaka, Hiromasa; Koretomo, Ryosuke; Ishikawa, Tomohiro
Abstract: The mass balance, pharmacokinetics, and biotransformation of JTZ‐951 (enarodustat), a novel hypoxia‐inducible factor prolyl hydroxylase inhibitor, were characterized in patients (N = 6) with end‐stage renal disease on hemodialysis. Following a 10‐mg (100 µCi) oral dose of 14 C‐JTZ‐951, whole blood, feces, dialysate, and, if feasible, urine were obtained for pharmacokinetic assessments and for metabolite profiling and identification in appropriate matrices. Fecal excretion was the major route of elimination of radioactivity, and urinary excretion a minor route, with mean (coefficient of variation [%CV]) recovery of 77.1 (16.2)% and 10.9 (92.0)% of the dose, respectively. Radioactivity was not detected in the dialysate, and mean (%CV) total recovery in excreta was 88.0 (14.9)%. For parent JTZ‐951 in plasma, the mean (%CV) effective half‐life was 8.96 (7.7)% hours, and area under the curve over 24 hours comprised the majority (>80%) of total exposure, with relatively low variability in these pharmacokinetic variables. Based on profiling of plasma radioactivity, parent JTZ‐951 was the predominant circulating component, accounting for 93.7% or more of radioactivity, and metabolite M2 (hydroxylated product) was the only detectable metabolite, but its exposure was minor (<5%) versus unchanged JTZ‐951. In urine and feces, the predominant analyte was JTZ‐951, and metabolite M2 was the predominant albeit minor metabolite, with small amounts of other metabolites. Thus, plasma exposure to drug‐derived radioactivity was primarily due to parent JTZ‐951, and the drug was cleared mainly by excretion of unchanged JTZ‐951. The study appropriately characterized the disposition of JTZ‐951 in patients with end‐stage renal disease.